The Implementation of a Telephone-Delivered Intervention for Asian American Disordered Gamblers: A Pilot Study - Parhami, Iman (2012)
This report will discuss the implementation and preliminary results of a community-based telephone-delivered gambling treatment program specifically designed for Asian Americans. The intervention was implemented by the NICOS Chinese Health Coalition, a nonprofit community organization based in Northern California, overseen by the UCLA (University of California, Los Angeles) Gambling Studies Program and the California Office of Problem Gambling, and launched in December 2010. It consisted of six 1-hr long telephone-delivered sessions conducted by a mental health provider using a translated version of the Freedom from Problem Gambling Self-Help Workbook. In the current study, 6 providers completed a 30-hr training program for gambling related disorders. One-hundred and 40 callers inquired about the intervention within the first 6 months of its launch, 19 clients expressed interest in participating, and 8 enrolled into the program. The results show that the majority of clients who enrolled into the program did not report any gambling behavior after baseline and improved on self-reported measures of overall life satisfaction, gambling urges, and self-control. This study suggests that the implementation of this type of intervention is feasible at a small community-based organization and may be effective in treating gambling-related disorders for Asian American populations. The low rate of clientele enrollment is addressed and potential remedies are discussed.